Investigation of imidazolinone herbicide towards weedy rice (Oryza sativa L.) and effects of its residual concentration in soil / Mahyoub Izzat Yousef Bzour - Mahyoub Izzat , Yousef Bzour (2020)
Clearfield® Production System (CPS) for rice was introduced in Malaysia in 2010 as the current best solution to combat weedy rice (Oryza sativa) especially in direct-seeding system using imidazolinone-based herbicide (commercial name: OnDuty®). Although CPS has widely implemented in many rice fields in Malaysia, some of the major concerns of CPS are the probability of weedy rice to become resistant to OnDuty® and herbicide residual effects to rice agro-ecosystems and other environments. Therefore, this study was aimed to (i) evaluate the resistant status of selected weedy rice biotypes to imidazolinone herbicide; (ii) determine association between weedy rice morphological characteristics with imidazolinone resistant; (iii) develop an HPLC method to extract imidazolinone herbicide from soil; and (iv) assess imidazolinone herbicide residues in CPS rice agro-ecosystem. Fresh weedy rice seeds from 17 biotypes were collected from IADA Barat Laut Selangor rice granaries. The resistant status of these biotypes with two control cultivars (i.e. MR220 [imidazolinone susceptable] and MR220-CL [imidazolinone tolerant]) were assessed by (i) seed bioassay and (ii) plant growth response methods with different concentrations of imidazolinone herbicide. Resistant levels based on injuries and major phenotypic traits of weedy rice were recorded. Germination test on seeds showed that all weedy rice biotypes have more than 60% germination rate on all herbicide concentrations. However, the viability of the un-germinated seedlings was relatively low indicating that this herbicide is effective as a pre-germination herbicide. Only 24% of weedy rice biotypes showed susceptibility to one-dose OnDuty® application while the rest displayed various resistant levels. The number of resistant weedy rice reduced to only six biotypes after double-dose application with more than 80% survival rate. This indicates that certain biotypes of weedy rice in Malaysia with wide phenotypic variation has developed resistant to imidazolinone herbicide in CPS rice fields. Samples were also taken from three Clearfield® rice fields as IMI- herbicides which have been used for six years at three different locations in Sawah Sempadan,Tanjung Karang, Malaysia. High performance liquid chromatography (HPLC) with UV detection and solid-phase extraction (SPE) cartridges, with two mobile phases was used to evaluate soil samples collected from CPS rice fields to assess imidazolinone herbicide residues (imazapic and imazapyr) in the soil. Results revealed minor herbicide residues in the CPS soil except areas near the edge of the fields where values recorded were above the residual threshold for imidazolinone. The average percentage recovery for imazapyr and imazapic varied from 76-107% and 71-77%, with 0.1-5 μg/mL fortification level, respectively. In the extracted soil sample residues of imazapic and imazapyr were found to fall within 0.04-0.5μg/mL for imazapic and from 0.03-1.9 μg/mL for imazapyr, respectively. This study showed rapid evolutionary of weedy rice to develop resistant or adapt with environmental changes in rice agro-ecosystems. Various possibilities of weedy rice ‘escape’ from CPS were discussed including weedy rice genotypic/phenotypic variation, and farmer’s attitude towards CPS. Despite low imidazolinone residues recorded in the CPS fields, the environmental impact of this system cannot be neglected, and further monitoring need to be done.